TAHAP-TAHAP PENYUSUNAN MODUL AJAR KURIKULUM MERDEKA TINGKAT SEKOLAH - Fatmawati Fatmawati; Lathifatuddini Rusdi; Ainol Mardhiah; Putri Husna; Fuady Fuady (Universitas Pahlawan Tuanku Tambusai, 2022)
Kurikulum Merdeka is initiated by Nadiem Makarim, the Minister of Education, aiming to return the authority of educational management to local governments and schools in accordance with local’s needs, capacities, and wisdom. Even though this curriculum was officially launched in February 2022, until now, teachers in Indonesia, especially teachers at SD Negeri Pertiwi, Lamgarot Aceh Besar, are still unfamiliar, especially with regard to teaching modules based on this Kurikulum Merdeka. Therefore, lecturers from several universities in Aceh were inspired to assist these teachers through a socialization and teach the teachers about the stages of preparing teaching modules. This activity aims to increase teachers’ capacity in compiling independent curriculum teaching modules so that they can focus on being learning facilitators. The method used was socialization through lectures. The results of this activity indicated that there was an increase in the knowledge and skills of SD Negeri Pertiwi, Lamgarot, Aceh Besar teachers in compiling teaching modules based on Kurikulum Merdeka. Keywords: Kurikulum Merdeka, teaching module, socialization